Effect of adhesive modification on the SLJ strength for disassembly purposes - Yap, Wai Ren (2019)
Adhesive joints are replacing traditional fastening methods like nuts and bolts due to their lower weight and ability to provide a highly uniform distribution of stress along the joined area. However, the disassembly of joints differs from the conventional methods and requires some modifications to ensure little or no damage to the bonded structures. Most of the current methods utilise heat energy as the main driving mechanism to cause debonding, for example, the use of heat to cause expansion in thermally expandable particles (TEPs) or the use of electrical means to generate heat to degrade the adhesive. The effect of TEPs on the strength of an adhesive has not been clearly defined and the heating capacity of carbon scrim in an adhesive joint when electrical voltage is applied has not been fully explored. The aim of this study was to identify the effect of physical foaming agents (PFA) in epoxy adhesives and to evaluate the heat delivery capacity of carbon scrims in hybrid adhesively bonded joints. The dynamic mechanical analysis (DMA) was first conducted to characterise the glass transition temperature (Tg) and storage moduli of the various concentrations of Expancel 920 DU 40 microspheres (0 wt%, 5 wt%, 10 wt% and 25 wt%) incorporated in 3M™ DP490 adhesive. The morphology of the samples was also analysed with a scanning electron microscope (SEM) to further support the speculations from the DMA test. Single lap bonded joints (SLJ) were then fabricated with the same concentrations and tested at the activation temperature (130oC) of the fillers. Finally, the heat delivering capacity of carbon scrims was tested in various configurations – Carbon scrim only, carbon scrim with Henkel Hysol® EA9696 adhesive, carbon scrim with EA9696 and Carbon Fibre Reinforced Polymer (CFRP) and carbon scrim with EA9696 and Ti-64-4V alloy. The DMA results showed that both the Tg and storage moduli increased by about 3.4% and 5.4% respectively with the addition of fillers up to 25 wt% except for the 10 wt%. This was due to poor interfacial adhesion between the fillers and the matrix, as supported by the SEM images. The single lap joints failed to produce reliable results as the activation temperature of the fillers was higher than the Tg of the epoxy, which turned the epoxy into a rubbery state during the test. The carbon scrim conductivity tests showed that carbon scrim bonded to only a layer of EA9696 adhesive produced the highest temperature (252.7oC), followed by the CFRP and scrim-only specimens. It was found that the varying thicknesses of the adhesives might have affected both the thermal conductivity and resistance of the joint, thus affecting the temperatures obtained.